Surveillance of transmitted HIV-1 drug resistance in Gauteng and KwaZulu-Natal Provinces, South Africa, 2005-2009 - Hunt, G M; Ledwaba, J; Basson, A E; Moyes, J; Cohen, C; Singh, B; Bertagnolio, S; Jordan, M R; Puren, A; Morris, L (Clinical infectious diseases, 2012)
Surveillance of human immunodeficiency virus type 1 transmitted drug resistance (TDR) was conducted among pregnant women in South Africa over a 5-year period after the initiation of a large national antiretroviral treatment program. Analysis of TDR data from 9 surveys conducted between 2005 and 2009 in 2 provinces of South Africa suggests that while TDR remains low (<5%) in Gauteng Province, it may be increasing in KwaZulu-Natal, with the most recent survey showing moderate (5%-15%) levels of resistance to the nonnucleoside reverse transcriptase inhibitor drug class.